Design and analysis of reinforced welded tubular joints - Hoon, Kay Hiang. (2008)
In this project, three dimensional finite element models were devised to study the hotspot stresses on a tubular round to round T-joint reinforced with a doubler plate under the basic axial tension and compression loading, in-plane bending (IPB) and out-of-plane bending (OPB).